Latent carbon emission pricing model for Thailand: A nonlinear autoregressive distributed lag model. (November 2022) - Tansuchat, Roengchai; Chang, Chia-Lin
Abstract: Nowadays, many scientific researchers confirm that carbon emissions cause global warming. Accurate carbon emission pricing is a direct economic measure of greenhouse gas emissions' actual cost or price. However, Thailand currently does not have a carbon emission price from the formal mandatory carbon market. This paper aims to calculate Thailand's latent carbon emission price based on the KLEM production function and Nonlinear Autoregressive Distributed Lag Model (NARDL). Used are the seasonally adjusted data on the volume of carbon emissions, energy resources, and energy prices from January 2009 to December 2020. The best fit model for NARDL (3, 4, 0, 4, 2, 0, 4, 2, 0), while that for the ARDL (2, 0, 4, 0, 0). In all cases considered, the average estimated monthly carbon emission prices lie in the range of 42.21–78.61. The calculated latent carbon emission price may differ depending on the proportion of the energy source and the energy price in each country.